The psychological mechanism of construction workers’ safety participation: The social identity theory perspective - Choi, Byungjoo; Lee, Sang Hyun (Journal of Safety Research, 2022)
Introduction: Safety participation has gained increasing attention as an important dimension of workers' safety behaviors. Although previous studies attempted to identify factors affecting workers’ safety participation, only a few studies paid attention to the psychological mechanisms behind it. Therefore, this study aimed to develop and test a research model that explains how management factors are implicated in workers' safety participation. Specifically, this study focused on project-based organizations (e.g., construction projects) because employee psychological mechanisms may have a unique nature in such transient employment. Method: The hypotheses in the research model of the psychological mechanism of construction workers' safety participation are tested using survey data from 261 construction workers. Results: The results indicated that construction workers' safety participation is influenced by project identification after controlling the shared variance of safety compliance. Project identification also mediates the effects of transformational leadership and communication climate on safety participation. Practical Applications: This study offers researchers and practitioners an explanation of how management factors influence construction workers' safety behaviors and clarifies the role of project identification play in explaining the effects of management factors on safety compliance and safety participation.
Keywords: Communication climate; Construction safety; Construction workers; Management factors; Project identification; Psychological mechanism; Safety behavior; Safety participations; Transformational leadership; Worker safety; Communication; Construction Industry; Health Behavior; Humans; Occupational Health; Social Identification; Surveys and Questionnaires; Communication climate; Construction safety; Project identification; Psychological mechanism; Safety participation; Transformational leadership